Revisiting race and ethnicity in Peru: intersectional and decolonizing perspectives. Issue 1 (2nd January 2022) - Cox Hall, Amy; Alcalde, M. Cristina; Babb, Florence E.
ABSTRACT: We introduce this special issue of LACES by first offering a critical overview of recent work that engages questions of race and ethnicity in Peru. Against the backdrop of contemporary developments at the national level, we argue for a decolonial, intersectional approach that recognizes and theorizes differences that are complex and cross-cutting, embracing not only ethnoracial but also gender-, class-, and sexuality-based differences. Contributors to this issue offer diverse perspectives on commingled vectors of difference and inequality in a variety of settings, from Andean communities to lowland, urbanizing contexts, and from coastal, cosmopolitan Lima to Peru's global diaspora. The pieces that follow our introduction include research articles, review essays, and interviews with performance artists and social activists, affording readers the opportunity to rethink with us the shifting landscape of race and ethnicity in Peru and beyond.